Role of the UNC13 family in human diseases: A literature review - Ubaid Ansari; Vincent Chen; Romteen Sedighi; Burhaan Syed; Zohaer Muttalib; Khadija Ansari; Fatima Ansari; Denise Nadora; Daniel Razick; Forshing Lui (AIMS Neuroscience, 2023)
This literature review explores the pivotal roles of the Uncoordinated-13 (UNC13) protein family, encompassing UNC13A, UNC13B, UNC13C, and UNC13D, in the pathogenesis of various human diseases. These proteins, which are evolutionarily conserved and crucial for synaptic vesicle priming and exocytosis, have been implicated in a range of disorders, spanning from neurodegenerative diseases like amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) to immune-related conditions such as familial hemophagocytic lymphohistiocytosis (FHL). The involvement of UNC13A in neurotransmitter release and synaptic plasticity is linked to ALS and FTD, with genetic variations affecting disease progression. UNC13B, which is closely related to UNC13A, plays a role in autism spectrum disorders (ASD), epilepsy, and schizophrenia. UNC13C is implicated in oral squamous cell carcinoma (OSCC) and hepatocellular carcinoma (HCC), and has a neuroprotective role in Alzheimer's disease (AD). UNC13D has an essential role in immune cell function, making it a key player in FHL. This review highlights the distinct molecular functions of each UNC13 family member and their implications in disease contexts, shedding light on potential therapeutic strategies and avenues for future research. Understanding these proteins' roles offers new insights into the management and treatment of neurological and immunological disorders.